Comparison of holmium laser enucleation with bipolar transurethral enucleation of the prostate in patients with benign prostatic hyperplasia: Results of a multicentre study. (14th March 2022) - Tuncel, Altug; Aykanat, Can; Akdemir, Serkan; Oksay, Taylan; Arslan, Murat; Başboga, Serdar; Aslan, Yilmaz; Balci, Melih; Guzel, Ozer
Abstract: To assess the efficacy and morbidity of the holmium laser enucleation of the prostate and bipolar transurethral enucleation of the prostate in patients with benign prostatic hyperplasia. The study included 60 (55%) and 49 (45%) patients who underwent laser and bipolar enucleation of the prostate respectively. According to the perioperative data, except for length of hospital stay and enucleated prostate weight, all the remaining parameters were similar between the groups. There were significant differences between the preoperative and the postoperative third and 12th month voiding parameters in both groups. In the laser group, the maximum urine flow rate value was better than the bipolar group at the postoperative third and 12th months. However, we did not find any statistically significant difference between the groups in terms of the serum prostate‐specific antigen level, International Prostate Symptom Score and postvoid residual urine volume at the postoperative third and 12th months. Our results show that both laser and bipolar techniques are effective minimally invasive surgical treatment options for men with benign prostatic hyperplasia. When compared to bipolar technique, laser technique provides shorter hospital stay, more prostatic tissue enucleation and better maximum urine flow rate values.